The Plagiarism in the Theses of English Education Students at Kabupaten Bone - Rizkariani Sulaiman (Universitas Cokroaminoto Palopo, 2015)
The topic of this study is “Plagiarism in the Theses of English Education Students: Forms and Causes. In this study, the researcher limits the discussion by the following research questions: “what are the forms of students’ plagiarism in theses? and what are the causes that make students engage in the plagiarism?”. The objective of the study is specifically to know the forms of students’ plagiarism in theses; and to know the causes that make students engage in the plagiarism. In order to achieve the objective of this study, the researcher applied descriptive quantitative research. The population of this study was the theses of English education students that were submitted in 2011 and lecturers from two colleges. As instrument of the research, plagiarism forms according to government rule No. 17, 2010 and duplichecker application used to investigate the first research question; and questionnaire used to investigate the second research question. The result of the study revealed that plagiarism type 1 was the dominant type occurred in students theses, followed by plagiarism type 2, 3 and 4; chapter 1 and 2 of most of the theses are the most frequent place for plagiarism types occurred; another type of plagiarism found was chained plagiarism; and the causes of students engage in plagiarism can be divided into four main causes: a) lack of knowledge in referencing and quoting; b) limited access of literature; c) attitude; and d) plagiarism is not managed yet administratively. In line with the result, the researcher suggests that plagiarism in colleges should be familiarized, socialized and actively founded; the students also should enrich the knowledge of referencing and paraphrasing; and colleges should try to organize the standard rule clearly and firmly and introduce plagiarism detectors to reduce the plagiarism action.